Efficacy of Zoladex LA (goserelin) in the treatment of girls with central precocious or early puberty. Issue 4 (1st October 1998) - Paterson, W F; McNeill, E; Reid, S; Hollman, A S; Donaldson, M D C
Abstract : OBJECTIVE: To assess the efficacy of a longer acting preparation of the gonadotrophin releasing hormone (GnRH) analogue goserelin (Zoladex LA, 10.8 mg) in 12 girls with central precocious or early puberty. METHODS: Two girls started treatment de novo; the remainder had been on suppressive treatment for a median duration of 1.5 (range, 0.2–5.6) years. Assessment comprising auxology, pubertal staging, and pelvic ultrasound examination was carried out at weeks 0, 4, 8, 10, and 12 (first cycle) and weeks 8, 10, and 12 (second cycle) to evaluate the required injection frequency. Thereafter, assessment was performed on the day of injection. Zoladex LA was given every 12 weeks unless pubertal progression occurred. RESULTS: Satisfactory control was achieved in eight patients using this regimen, and three patients required more frequent injections. One girl was removed from the study because of clinical progression and extreme mood swings. No serious adverse effects occurred. Mean height velocity during the study period was 4.5 cm/year (range, 3.1–6.6) compared with 6.5 cm/year (range, 3.8–9.6) before treatment in nine patients for whom data were available. CONCLUSIONS: Zoladex LA was effective in controlling precocious puberty in girls when given at intervals of 9–12 weeks and it is recommended that an initial assessment is made eight weeks after beginning treatment.